Singlet fission in heterogeneous lycopene aggregates - Chloe Magne; Vasyl Veremeienko; Roxanne Bercy; Minh-Huong Ha-Thi; Ana A. Arteni; Andrew A. Pascal; Mikas Vengris; Thomas Pino; Bruno Robert; Manuel J. Llansola-Portoles (Scientific Reports)
Abstract We have prepared lycopene aggregates with low scattering in an acetone–water suspension. The aggregates exhibit highly distorted absorption, extending from the UV up to 568 nm, as a result of strong excitonic interactions. We have investigated the structural organization of these aggregates by resonance Raman and TEM, revealing that the lycopene aggregates are not homogeneous, containing at least four different aggregate species. Transient absorption measurements upon excitation at 355, 515, and 570 nm, to sub-select these different species, reveal significant differences in dynamics between each of the aggregate types. The strong excitonic interactions produce extremely distorted transient electronic signatures, which do not allow an unequivocal identification of the excited states at times shorter than 60 ps. However, these experiments demonstrate that all the lycopene aggregated species form long-living triplets via singlet fission.